Evaluasi Kelayakan Platform Ucapan Digital dengan Metode Heuristic Evaluation - Gala, Aryatriwulan Buli; Chernovita, Hanna Prillysca (STMIK Banjarbaru, 2025)
The digital greeting platform of Satya Wacana Christian University (UKSW) was developed as an environmentally friendly solution to replace physical greeting media in ceremonial events. This study aims to evaluate the usability level of the platform using the Heuristic Evaluation method based on Nielsen and Molich’s ten principles. Data were collected through questionnaires distributed to five respondents and in-depth interviews with three of them. The evaluation results indicate five principles with the highest severity levels, namely Help and Documentation (3.8), Visibility of System Status (3.6), Error Prevention (3.6), User Control and Freedom (3.4), and Flexibility and Efficiency of Use (3.2). Identified issues include the absence of user guides, lack of process feedback, weak input validation, limited navigation, and minimal design variations. Recommended improvements involve adding a help page, process indicators, input validation, main navigation buttons, and more varied greeting templates. These findings confirm the effectiveness of heuristic evaluation in identifying interface weaknesses and provide guidance for developing a more user-friendly system.Keywords: Digital greeting platform; Heuristic Evaluation; Usability; User experience AbstrakPlatform ucapan digital Universitas Kristen Satya Wacana (UKSW) dikembangkan sebagai solusi ramah lingkungan untuk menggantikan media ucapan fisik pada acara seremonial. Penelitian ini bertujuan mengevaluasi tingkat usability platform tersebut menggunakan metode Heuristic Evaluation berdasarkan sepuluh prinsip Nielsen and Molich. Penilaian dilakukan melalui kuesioner kepada lima responden serta wawancara mendalam terhadap tiga di antaranya. Hasil evaluasi menunjukkan lima prinsip dengan tingkat keparahan tertinggi, yaitu Help and Documentation (3,8), Visibility of System Status (3,6), Error Prevention (3,6), User Control and Freedom (3,4), dan Flexibility and Efficiency of Use (3,2). Permasalahan yang ditemukan meliputi ketiadaan panduan penggunaan, tidak adanya umpan balik proses, lemahnya validasi input, keterbatasan navigasi, serta minimnya variasi desain. Rekomendasi perbaikan meliputi penambahan halaman bantuan, indikator proses, validasi format input, tombol navigasi utama, serta variasi template ucapan. Temuan ini menegaskan efektivitas evaluasi heuristik dalam mengidentifikasi kelemahan antarmuka serta memberikan arahan pengembangan sistem yang lebih user-friendly.Kata kunci: Platform ucapan digital; Heuristic Evaluation; Usability; Pengalaman pengguna